Basic life support training with high schools' teachers in Bahia, Brazil: an experimental study. (30th September 2020) - Vivas, T; Duarte, M; Puschel, V; Oliveira, H; Sales, P; Rocha, G; Oliveira, I
Abstract: Background: Early performing of cardiopulmonary resuscitation is the cornerstone of survival in out-of-hospital cardiac arrest, doubling the odds of survival when correctly performed. The American Heart Association and the European Resuscitation Council advocate for training the entire population in order to enable a quick and effective response to out-of-hospital cardiac arrests, improving its outcomes. In primary healthcare settings the health workers can act as trainers, using the family and territorial approach to deliver basic life support (BLS) basis to general population, assuring that key social actors are skilled enough to aid community when needed. This study aims to compare the knowledge and practice skill of high school teachers before and after a BLS training delivered by health workers and students in a primary healthcare setting. Methods: Teachers of three public high schools in Bahia, Brazil were assessed by a test for theoretical and practical skill in BLS and then trained by a group of primary care workers and students. Training included a 20min lecture and 40min practice session in a simulated scenario. After the training the teachers were assessed with the same test for theoretical and practical skill. A paired-samples T test was used to detect the difference in the mean total score before and after the training, with a significance level of 0.05 (two-sided test) and 95% confidence interval. Results: The mean total score after the BLS training (8.2 ± 1.5) was significantly higher (p < 0.000) from before training (4.5 ± 1.7). Conclusions: The high school teachers were unable to deliver proper cardiopulmonary resuscitation before the intervention. Following a BLS training a significant immediate improvement in the knowledge and practical skill was detected. Health workers were able to achieve these results in a primary healthcare setting. Further studies should assess this outcome with larger samples, evaluating the retention of knowledge and skills provided. Key messages: Basic life support training can be delivered to general population by health workers in primary healthcare settings in order to improve the outcomes to out-of-hospital cardiac arrests. Teachers and health workers can act as key actors in intersetorial health-education initiatives, promoting the health of their communities.